Analysis of the Cusco provincial municipal management 1999-2002, recovery of public spaces - Barrio de San Pedro - Ciprian Collantes, Edwin (2021)
This article analyzes the Management of the Municipal Government of the period 1999-2002, which was chaired by the former mayor of the city of Cusco, Ing. Carlos Valencia Miranda, who started under the phrase "Cusco city with a future". This research focuses on the four management components such as: Management and Administration Framework, Planning, Legal and Financial Mechanisms and International Cooperation. Municipal management occurs at a political junc- ture of changes, starting the process of decentralization and regionalization, thanks to the Organic Law on Municipalities (No. 27972) already repealed. Likewise, in this management course it is important to mention the participation of other non-governmental public and private sector institutions who collaborated on the heritage issue for this management.